Spiritual Integration Predicts Self-Reported Mental and Physical Health - Rogers, Darrin L. (Journal of religion and health, 2012)
Data from 167 participants were used to establish the psychometric properties of the Reidhead spiritual integration scale, 31-item version (SI-31). Structural equation modeling was used to empirically evaluate influences on perceived health functioning, while accounting for possible confounds. The analyses showed that SI-31 predicted perceived mental and physical health while controlling for life satisfaction, religious variables, mood patterns, depression symptoms, and demographics. The importance of SI as a predictor of health-related outcomes is supported, as is the usefulness of the SI-31 in predicting these outcomes.